2020
DOI: 10.3390/su12073039
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Consumer Preference for Milk Produced through Sustainable Farming: The Case of Mountainous Dairy Farming

Abstract: As income is rising and urbanization progressing, the consumption of meat and dairy products is increasing, especially in developing countries. However, increasing livestock production leads to challenges that need to be addressed, such as yielding environmental pollution and causing climate change. Due to these circumstances, the importance of sustainable livestock farming has been highlighted in order to effectively utilize natural resources and to protect the environment. We analyzed consumers’ preference a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
(18 reference statements)
1
12
1
Order By: Relevance
“…Moreover, in contrast to previous work (Nam et al 2020), purchase intention showed to be higher among consumers with a mid-level income. This counterintuitive result can be related to the perception of the mountain product as an expensive but not luxury good.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, in contrast to previous work (Nam et al 2020), purchase intention showed to be higher among consumers with a mid-level income. This counterintuitive result can be related to the perception of the mountain product as an expensive but not luxury good.…”
Section: Discussioncontrasting
confidence: 99%
“…A number of technological factors that determine the production cost and ultimately the result of the production process, affect the performance of livestock complexes and farms for the production of raw milk. It is important to consider the economic feasibility of performing dairy farming by building consensus with consumers, by studying marketing preferences when interacting with possible changes in technological operations, making products with higher consumer properties to ensure a stable level of the production and economic process of the industry and increase the product competitiveness [5,10].…”
Section: Resultsmentioning
confidence: 99%
“…For food products of animal origin, some studies have investigated the effect of information about the production method, demonstrating that information about cow grazing versus information about indoor system increased consumer preference for meat [ 23 , 24 ] and generated the highest willingness to pay or positive effect, in terms of liking milk [ 25 , 26 , 27 , 28 ]. Romanzin et al [ 28 ] have reported similar results for cheese, even if the literature on this food matrix is scarce.…”
Section: Introductionmentioning
confidence: 99%